Analytical analysis of the magnetic field, heat generation and absorption, viscous dissipation on couple stress casson hybrid nano fluid over a nonlinear stretching surface - Nabila Hameed; Samad Noeiaghdam; Waris Khan; Busayamas Pimpunchat; Unai Fernández‐Gámiz; Muhammad Sohail Khan; Ali Rehman (Results in Engineering, 2022)
The aim of this research paper is to study two-dimension flow of Casson hybrid nanofluid along with magnetic field, heat generation and absorption, and viscous dissipation on a nonlinear extending surface. The primary goal of this study is to improve the heat transfer relationship, which is in high demand in the manufacturing and engineering industries. The outputs of this study will be used to reduce the energy consumption in industry and other engineering fields,for example, the achievement of energy is not enough, but also to adjust the consumptions of energy and this is possible only to approve the development heat transmission liquids to mechanism the expenditures of energy and to improvement. The described similarity transformation is used to convert the non-dimensionless form of the nonlinear partial differential equation to the dimensionless form of the nonlinear ordinary differential equation. An approximate analytical method is used to solve the derived dimensionless form of nonlinear ordinary differential equations, one for velocity and the other for temperature. Graphs are used to highlight the most relevant results acquired from velocity and temperature. Tables are used to describe the skin friction coefficient and the Nusselt number.
Keywords: Nanofluid Flow and Heat Transfer; Heat Transfer Mechanisms; Heat Transfer and Optimization